P1184TRANSVERSUS ABDOMINIS PLAIN BLOCK RELIEVES PERIOPERATIVE PAIN ON PERITONEAL DIALYSIS CATHETER INSERTION: A RANDOMISED CONTROLLED STUDY. (6th June 2020) - Harada, Kenji; Kanai, Hidetoshi
Abstract: Background and Aims: The effectiveness of Transversus Abdominis Plain (TAP) block has been reported in the pain control at abdominal operation. However, its usefulness in pain management remains unclear in peritoneal dialysis (PD) patients undergoing catheter insertion. We investigated the effectiveness and safety of TAP block for perioperative on PD catheter insertion. Method: The present study is a single-centred, prospective, randomised study of initiated PD patients between from October 2017 to January 2020. VAS (Visual Analogue Scale), which is often used around anesthesiology and pain management area, was measured as pain assessment. VAS was measured at five points, right after and 1, 3, 6, 24 hours after operation, using t-test with P values. Results: Overall, 106 PD patients were included (mean age; 63.8 years old, male/female; 81/25, average eGFR 7.54±2.64). Patients were divided into two groups TAP block (n=50) and non-TAP block (n=56). There were significantly low VAS in TAP block group right after operation (1.39 vs 2.88, p=0.0035) and 1 hour after operation (1.86 vs 3.19, p=0.0078). Furthermore, total five points of VAS were significantly low VAS in TAP block group (10.59 vs 13.85, p=0.028). There were no cases needed for ventilation and anesthetic drug such as morphine. TAP block-related adverse events were not found. Conclusion: TAP block technique was significantly associated with relief from post-operative pain in PD catheter insertion. This treatment procedure might be a minimally invasive and effective therapeutic option for perioperative pain management on PD catheter insertion.